2012
DOI: 10.1177/1757177412462047
|View full text |Cite
|
Sign up to set email alerts
|

Improving public perceptions around cleanliness and health care associated infection in hospitals (service improvement)

Abstract: Peer reviewed articlequalitative study was undertaken to understand public perceptions of hospital cleanliness and how this might be improved following national initiatives to reduce infection rates and invest in domestic services. Eleven focus groups were held across the West Midlands.Results demonstrated that perceptions are attained from a variety of sources. For patients and visitors the things they see, hear, smell and taste in hospitals and health services shaped their perceptions of cleanliness. For the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(41 citation statements)
references
References 7 publications
0
41
0
Order By: Relevance
“…Most of these studies are about the managerial side of cleaning by focussing on the make or buy decision for cleaning services (e.g., Klungseth et al, 2016, Houston & Youngs, 1996, Gbadegesin & Babatunde, 2015, end-user satisfaction with cleaning services (e.g., Hui et al, 2013, Hui & Zheng, 2010, and cost management (e.g., Bywater, 1990). The qualitative studies of Whitehead et al (2007) and Whatley et al (2012) are to the knowledge of the authors the only studies evaluating the effect of cleaning staff on end-user perceptions. In both studies, the presence of cleaning staff and more specifically the appearance, behaviour, and attitude of cleaning staff were identified as 'social cues' that positively influence perceptions of cleanliness.…”
Section: Presence Of Cleaning Staffmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of these studies are about the managerial side of cleaning by focussing on the make or buy decision for cleaning services (e.g., Klungseth et al, 2016, Houston & Youngs, 1996, Gbadegesin & Babatunde, 2015, end-user satisfaction with cleaning services (e.g., Hui et al, 2013, Hui & Zheng, 2010, and cost management (e.g., Bywater, 1990). The qualitative studies of Whitehead et al (2007) and Whatley et al (2012) are to the knowledge of the authors the only studies evaluating the effect of cleaning staff on end-user perceptions. In both studies, the presence of cleaning staff and more specifically the appearance, behaviour, and attitude of cleaning staff were identified as 'social cues' that positively influence perceptions of cleanliness.…”
Section: Presence Of Cleaning Staffmentioning
confidence: 99%
“…To conclude, research in facilities management on the effects of the presence of cleaning staff on end-user perceptions is limited. The qualitative work available (Whitehead et al, 2007, Whatley et al, 2012 demonstrated that the presence of cleaning staff in the service environment might be beneficial for end-users.…”
Section: Presence Of Cleaning Staffmentioning
confidence: 99%
See 1 more Smart Citation
“…Scent, lighting, use of materials, density, and the condition of the environment (i.e., deterioration, aesthetics, architectural order) were identified in literature as antecedents influencing the appearance of the environment. The absence of unpleasant scents and the presence of pleasant scents were expected to positively influence perceptions of cleanliness (Whatley et al, 2012). Molenaar and Hu (2013) found that an environment is perceived as cleaner when lighting is pointed at traces of litter.…”
Section: Influencing End-user Perceptions Of Cleanlinessmentioning
confidence: 99%
“…The study contributes to the understanding of the concept of end-user perceptions of cleanliness and antecedents that influence perceived cleanliness. Compared to similar studies of Whitehead et al (2007) and Whatley (2012), we have taken a broader perspective by focussing not on the healthcare sector and end users (i.e., patients and medical staff) only, but instead focus on the FM sector as a whole by consulting end users and experts with different backgrounds. The results of this study are applicable to different types of service environments, however, the relative importance of the antecedents may vary depending on the type of environment and end user.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%